KONTEKS BERPOLITIK UMAT ISLAM DI INDONESIA - Arifin, Syamsul (Jurnal Bestari, 1994)
Historically, moslems were the grear del of Indonesian people. Until recent times, they have a most strategic powers quantitatively. Unfortunely, it does not accompanied by their real role in the light of qualitative aspect. It can be traced into the economic and political authorities. Indonesian moslems, therefore, must reconstruct their real life to do the best for glory of Islam. They have to engineer a modern exaggeration of their teachings to manifest politcal engineering.